1992
DOI: 10.1523/jneurosci.12-07-02745.1992
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen suppresses mu-opioid- and GABAB-mediated hyperpolarization of hypothalamic arcuate neurons

Abstract: The effects of estrogen on the response of hypothalamic arcuate neurons to mu-opioid and GABAB agonists were investigated. Intracellular recordings were made from arcuate neurons in slices prepared from ovariectomized guinea pigs that were pretreated with estrogen or vehicle. Estrogen shifted the dose-response curve to the mu-opioid agonist DAMGO (Tyr-D-Ala-Gly-MePhe-Gly-ol) by 3.4-fold; the EC50 for DAMGO was 240 +/- 25 nM in estrogen-treated females versus 70 +/- 12 nM in the controls. The maximal hyperpolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(82 citation statements)
references
References 27 publications
3
79
0
Order By: Relevance
“…The mechanism of estrogenic modulation of opioidergic tone does not seem to involve changes in the affinity and/or number of hypothalamic Jo receptors (Zhang et al, 1993). Instead, we have previously shown that a 24 hr treatment of ovariectomized guinea pigs with estradiol benzoate in vivo leads to a threefold reduction in w-opioid potency compared with oil-treated controls (Kelly et al, 1992). In the present study, in vitro exposure of hypothalamic slices to E, was used to characterize further the time course and concentration dependence of this, or a similar, estrogenic effect.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The mechanism of estrogenic modulation of opioidergic tone does not seem to involve changes in the affinity and/or number of hypothalamic Jo receptors (Zhang et al, 1993). Instead, we have previously shown that a 24 hr treatment of ovariectomized guinea pigs with estradiol benzoate in vivo leads to a threefold reduction in w-opioid potency compared with oil-treated controls (Kelly et al, 1992). In the present study, in vitro exposure of hypothalamic slices to E, was used to characterize further the time course and concentration dependence of this, or a similar, estrogenic effect.…”
mentioning
confidence: 80%
“…Furthermore, our previous work has shown that a 24 hr exposure to estradiol results in a reduced DAMGO potency in all of the ARC neurons that were tested (Kelly et al, 1992). Thus, there may also be a time dependence to this regulation of endogenous opioids.…”
Section: Potential Mechanisms Of E Actionmentioning
confidence: 93%
See 1 more Smart Citation
“…Both μ-opioid receptor (e.g., by β-endorphin or by selective μ-opioid agonists) or GABA B receptor activation of these GIRK channels directly hyperpolarize and thereby inhibit hypothalamic neurons (Loose et al, 1990, Kelly et al, 1992, Lagrange et al, 1994, Lagrange et al, 1995, Lagrange et al, 1996. Brief (<20 min) application of E2 or BSA-E2 in vitro causes a four-fold decrease in the potency of μ-opioid receptor agonists and GABA B receptor agonists to inhibit POMC neurons (Lagrange et al, 1994, Lagrange et al, 1996, indicating that a membrane ER (mER) is involved.…”
Section: Effects Of 17β -Estradiol On Vmh and Arcuate Neurons: Role Imentioning
confidence: 99%
“…Receptor protein regulation through the genomic action of steroids and the consequences on modulating neurotransmission are established at time scales beyond the phenotypical properties of neurons controlling the expression of stimulus driven behavior. However, as steroids can also modulate the acute effects of m-opioid agonists on potassium membrane conductance at the membrane level (Kelly et al, 1992), thereby influencing interspike intervals of action potentials by membrane hyperpolarization, a more causal involvement of receptor efficacy in regulating the ''shaping'' of behavior can be expected.…”
Section: Opiate-receptor Binding Steroidal Effects On Calling Patternsmentioning
confidence: 99%